2016
DOI: 10.1016/j.cell.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Control of Brainstem Locomotor Circuits by Basal Ganglia

Abstract: Summary The basal ganglia (BG) are critical for adaptive motor control, but the circuit principles underlying their pathway-specific modulation of target regions are not well understood. Here, we dissect the mechanisms underlying BG direct- and indirect-pathway-mediated control of the mesencephalic locomotor region (MLR), a brainstem target of the BG that is critical for locomotion. We optogenetically dissect the locomotor function of the three neurochemically-distinct cell types within the MLR: glutamatergic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
514
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(553 citation statements)
references
References 57 publications
34
514
5
Order By: Relevance
“…The strong inputs to CnF-Vglut2-Ns from PAG (especially the dorsal part), inferior colliculus, and hypothalamus, are in accordance with previous anatomical findings 12 and suggest that CnF-mediated fast locomotion may be generated as part of an escape response independent of the PPN. As previously shown, PPN neurons receive rich projection from basal ganglia nuclei 12,14 , but also from many midbrain and medullary sensory-motor nuclei as well as from motor cortex. This innervation pattern is in accordance with a role of glutamatergic PPN neurons for exploratory locomotor behaviour under the motor action selection of the basal ganglia 30,31,32,33,34,7 .…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The strong inputs to CnF-Vglut2-Ns from PAG (especially the dorsal part), inferior colliculus, and hypothalamus, are in accordance with previous anatomical findings 12 and suggest that CnF-mediated fast locomotion may be generated as part of an escape response independent of the PPN. As previously shown, PPN neurons receive rich projection from basal ganglia nuclei 12,14 , but also from many midbrain and medullary sensory-motor nuclei as well as from motor cortex. This innervation pattern is in accordance with a role of glutamatergic PPN neurons for exploratory locomotor behaviour under the motor action selection of the basal ganglia 30,31,32,33,34,7 .…”
Section: Resultssupporting
confidence: 55%
“…No locomotion was induced by stimulation of the local inhibitory neurons in PPN and CnF 14 or the cholinergic cells in PPN while their activation slowed or stopped on-going locomotion (Extended data Fig. 3a–c).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that glutamatergic cuneiform nucleus neurons were able to drive the full range of locomotor gaits — walk, trot, bound and gallop — and speed. Glutamatergic pedunculopontine nucleus neurons could only trigger low speed locomotion when stimulated at high intensity, whereas stimulation of cholinergic pedunculopontine nucleus neurons was insufficient to initiate locomotion, as shown by Roseberry et al [9]. …”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
“…Roseberry et al [9] pioneered the dissection of mesencephalic locomotor region heterogeneity, by showing that optogenetic activation of glutamatergic neurons was sufficient to transition the mouse from a stationary state to walking, whereas stimulating glutamatergic and cholinergic mesencephalic locomotor region neurons triggered a transition from walking to running; conversely, the inhibition of glutamatergic neuron activation halted or decelerated locomotion.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%